Exploring Knowledge and Attitudes on Gerontology Among Muslim Gifted and Talented Students - Marsya Safiyya Mohd Syaiful Azli; Wan Arisha Amirah Wan Mohd Zamri; Rosita Zainal; Asmuje, N.F (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025